The Influence of Organizational Culture and Ethics on Public Services at the Medan Satria District Office - Penny Fitri Hapsari; Agus Cholik; Muhammad Rifnaldi; Hardiansyah; Ami Setiasih (International Publisher, 2024)
This study aims to analyze the influence of organizationalculture and ethics on the quality of public services at theMedan Satria District Office. Using a quantitativeapproach and survey method, this study involved 200respondents selected through random samplingtechniques from the community using services in MedanSatria District. Data were collected through a structuredquestionnaire and analyzed using multiple regressionanalysis. The results of the study show that organizationalculture has a positive and significant influence on publicservices with a determination coefficient of 0.642(p<0.05), while ethics contributes positively with a valueof 0.583 (p<0.05). Simultaneously, these two variablesinfluence the quality of public services by 71.5%. Thisfinding indicates the importance of strengtheningorganizational culture and implementing service ethics inimproving the quality of public services at the sub-districtlevel. Research recommendations emphasize thedevelopment of employee training programs andstandardization of ethics-based service procedures.